Measurement of the t(t)over-bar production cross section in p(p)over-bar collisions at root s=1.96 TeV using lepton plus jets events with lifetime b-tagging - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (Elsevier B.V., 2005)
We present a measurement of the top quark pair (t (t) over bar) production cross section (sigma(t (t) over bar)) in pp collisions at root s = 1.96 TeV using 230 pb(-1) of data collected by the DO experiment at the Fermilab Tevatron Collider. We select events with one charged lepton (electron or muon), missing transverse energy, and jets in the final state. We employ lifetime-based b-jet identification techniques to further enhance the t F purity of the selected sample. For a top quark mass of 175 GeV, we measure sigma(t (t) over bar) 8.6(-1.5)(+1.6) (stat. + syst.) +/- 0.6(lumi.) pb, in agreement with the standard model expectation. (c) 2005 Published by Elsevier B.V.